Evaluation of QoL in cities of diverse neighbourhood typologies: A scientific study of New Delhi. Issue 2 (4th May 2021) - Mittal, Shilpi; Chadchan, Jayprakash; Mishra, Sudipta K
ABSTRACT: Quality of life (QoL) in urban areas is increasingly finding prominence in practice. There are numerous studies interlinking residential built environment and QoL at the city level but very few at the suburban level particularly for neighbourhoods. This research aims to prepare an analytical framework and a mathematical model to evaluate neighbourhood QoL as a function of its varying built environment and spatial attributes. In order to demonstrate this, a study is carried out for seven neighbourhood typologies of New Delhi by collecting data for both objective and subjective dimensions. The database is then analysed using statistical techniques of comparative analysis, correlation and regression analysis. The research indicates that (a) Quality of life within a city varies substantially at the neighbourhood level, and (b) current planning standards provide static city-wide benchmarks which are not attainable by most of the Indian neighbourhoods.